Expanding the discussion on internal management of risk communication: A critique of the current risk communication literature. (September 2021) - Lemon, Laura L.; VanDyke, Matthew S.
The purpose of this paper is to build from the infrastructural approach to risk communication, rethink the internal management of risk communication, and critique the current literature's discussion of how risks emerge, the role of the risk communication manager, and the decentralization of the risk communication function. Some of the risk communication literature is too general in terms of recognizing the nuance of the locus of risk, and the role(s) of stakeholders and communicators, which limit understanding that could extend and enrich current risk communication literature. In doing so, the conceptualization of where risk may occur broadens and research-based recommendations are developed from varied contexts to offer specific guidelines for future research to better understand the role of "internal" in risk communication and its practice. All of these points are not to diminish previous risk communication scholarship, but rather to refine and complement the current understanding so the management and communication of risk continues to enhance society as a whole.